The effectiveness of Super Absorbent polymers and superplasticizer in self-healing of cementitious materials. (30th August 2020) - Sidiq, Amir; Gravina, Rebecca; Setunge, Sujeeva; Giustozzi, Filippo
Highlights: Water-SAP absorption susceptivity was studied varying the superplasticizer content. Cracks were induced by controlling the damage level. Healing was assessed for single cracks throughout the volume of the sample. An innovative X-ray analysis method was developed for concrete healing assessment. Abstract: Concrete is susceptible to cracking typically under tensile stresses which reduces the mechanical resistance and endangers the overall durability of the structure. In this study, Super Absorbent Polymers are used with varying superplasticizer content to evaluate the efficiency of self-healing concrete. In-house fabricated mould is presented that induces controlled crack patterns in the entire volume of the sample. Self-healing efficiency is evaluated by conducting mechanical and non-destructive tests. In addition, X-ray tomography images are reconstructed into a 3-dimensional section to evaluate single crack closure and self-healing potential via porosity and sphericity analysis of cracks, including the reduction in crack width and the volumetric size of single cracks. The experimental results demonstrated that crack width up to 234 µm was healed with the addition of 2.2% superplasticizer content by weight of cement.